Efficient deep-blue non-doped organic light-emitting diode with improved roll-off of efficiency based on hybrid local and charge-transfer excited state. Issue 74 (22nd July 2016) - Liu, Haichao; Bai, Qing; Li, Weijun; Guo, Yachen; Yao, Liang; Gao, Yu; Li, Jinyu; Lu, Ping; Yang, Bing; Ma, Yuguang
Abstract : Acceptor–donor–acceptor triphenylamine–phenanthroimidazole derivate (TPA–2PPI) servers as an emitter, whose device exhibits deep-blue emission, high efficiency and slow roll-off of efficiency. Abstract : High-efficiency deep-blue light-emitting materials are of significance in the fields of commercial full-color displays and solid-state lightings. A hybrid local and charge-transfer (HLCT) excited state not only favors deep-blue emission avoiding a large redshift from a strong charge-transfer (CT) state, but also simultaneously harvests both high photoluminescence efficiency and high exciton-utilizing efficiency. Herein, we report a new V-shaped acceptor–donor–acceptor (A–D–A) type molecule TPA–2PPI with an HLCT emissive state, which is modified from D–A type TPA–PPI. The non-doped device based on the TPA–2PPI emitter still exhibits deep-blue emission peaking at 452 nm with a full width at half maximum (FWHM) of only 50 nm and Commission International de L'Eclairage (CIE) coordinates of (0.151, 0.108). Compared with TPA–PPI, the electroluminescence (EL) not only maintains high efficiency with a maximum external quantum efficiency (EQE) of 4.91%, but also the EL device displays a significantly slower roll-off of efficiency at high luminances with an EQE of 4.89% (or 4.56%) at 100 cd m −2 (or 1000 cd m −2 ), which is confidently beneficial for the operative stability of OLED devices.